Trend growth, unemployment and optimal monetary policy - Wolfgang Lechthaler; Mewael Tesfaselassie (Kiel Institute for the World Economy (IfW), 2015)
We analyze the implications of changes in the trend growth rate for optimal monetary policy in the presence of search and matching unemployment. We show that trend growth in itself does not generate a trade-off for the monetary authority, but that it interacts importantly with the inefficiencies stemming from the labor market. Higher trend growth exacerbates the inefficiencies of the labor market and therefore calls for larger deviations from price stability.
Keywords: E12; E24; E52; 330; trend growth; trend inflation; unemployment